Learning, Scholarship and Public Libraries in Pre and Colonial Sudan - Mustafa, Al haj Salim (European Scientific Journal, ESJ, 2017)
Although the idea of providing public library services to the general public is basically a westernized concept, nevertheless the Sudan has a long tradition of learning and scholarship in which one could argue that an embryonic and rudimentary public library service of some sort had been established. The purpose of this paper is to provide an historical overview of this learning and scholarship development and to explore the forces social, historical and political that led to the emergence of public libraries in pre and colonial Sudan. The historical research method was used to describe such forces employing mainly books, journal articles and to a lesser extent theses and dissertation. This will be followed by a discussion and conclusion.